2016
DOI: 10.1021/acsnano.6b00509
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Fabrication of Free-Standing Conducting Films with Hierarchical Surface Wrinkling Patterns

Abstract: Mechanical instability has been shown to play an important role in the formation of wrinkle structures in biofilms, which not only can adopt instability modes as templates to regulate their 3D architectures but also can tune internal stresses to achieve stable patterns. Inspired by nature, we report a mechanical-chemical coupling method to fabricate free-standing conducting films with instability-driven hierarchical micro/nanostructured patterns. When polypyrrole (PPy) film is grown on an elastic substrate via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 49 publications
8
43
0
Order By: Relevance
“…Additionally, compared with the bulk film surface, more space from the interior swollen PANI film is available to trigger the oxidative polymerization of the internally embedded pyrrole. As a result, interpenetrated PANI-PPy networks are formed, which is very similar to our previous report of the in-situ self-reinforced wrinkling PPy film with the interpenetrated networks43. The existence of the interpenetrated PANI-PPy networks and the corresponding decisive role will be discussed subsequently in more detail.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, compared with the bulk film surface, more space from the interior swollen PANI film is available to trigger the oxidative polymerization of the internally embedded pyrrole. As a result, interpenetrated PANI-PPy networks are formed, which is very similar to our previous report of the in-situ self-reinforced wrinkling PPy film with the interpenetrated networks43. The existence of the interpenetrated PANI-PPy networks and the corresponding decisive role will be discussed subsequently in more detail.…”
Section: Resultssupporting
confidence: 89%
“…S3. Recently, we have reported a self-wrinkling PPy film on the PDMS substrate with the self-stabilized two-scale wrinkling patterns43. It has been identified that the formation of interpenetrated networks modifies the stresses of the wrinkling PDMS/PPy system and thus stabilizes the self-wrinkling patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the surface of each micropapilla, nanofolds are evenly distributed and oriented in the longitude (Figure 1e). Owing to in situ self‐wrinkling happening during PPy deposition on the PDMS stamp,22,46 nanowrinkled PPy film is formed on the nanofolds of the PDMS stamp (Figure 1b–e), which is certified by the recorded scanning electron microscope (SEM) images of each preparation step (Figure S2a–d, Supporting Information) as well as the control experiment with the PPy deposition replaced by a fluorocontaining silane (Figure S2e, Supporting Information). As a result, rougher and more hierarchical surface morphologies occur on the 2nd PPy‐deposited PDMS stamp (Figure 1e), in comparison with the 2nd replicated PDMS stamp before the PPy deposition (Figure S2c,d, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…22,27 To improve the performance of CPs, a diverse set of architectures have been adopted and applied, because well-defined architectures are highly important in materials science, nanotechnology and bioengineering. 19,[28][29][30] However, direct and precise patterning of various architectures is still a major challenge because the conventional technologies that are used to produce designed polymers have poor reproducibility and involve multiple fabrication steps, which makes the process expensive, time-consuming and difficult to scale-up. 30 In this study, inspired by the functional features of plants, such as the bending of the pulvinus in M. pudica, the gating of stomata in leaf, and the selective filtering of the cellular membrane, a multifunctional hybrid membrane (HM) with thermo-responsive and conductive properties was adaptively synthesized with poly(N-isopropylacrylamide) (PNIPAm) and poly(pyrrole) (PPy), to enhance the functionalities of conventional CP hydrogels.…”
Section: Introductionmentioning
confidence: 99%